Niepokój Sartre’a, trwoga Abrahama, pies Dostojewskiego. Od tragizmu wyboru do egzystencjalnej hermeneutyki oraz powieściowej „mądrości niepewności” - Jakubowski, Piotr (Załącznik Kulturoznawczy, 2023)
The main aim of this article is to discuss some common and tragic human fate, that is making the decisions in state of incertitude (of our real motivations as well as of further consequences of our choices), and especially natural human’s reactions to them, that is searching the hints how to proceed (inside us, from authority, from ‘the signs of the world’). The examples taken to analyse are: Biblical story of Abraham (Do I really hear the voice of God telling me to kill my son?), philosophical story of Sartre’s disciple (Should I join to the resistance or stay with my sick mother?), and literary story of Dostoyevsky, taken from J.M. Coetzee’s novel Master of Petersburg (How to refine the voice of revelation from the hum of world?). Philosophical considerations are connected with narrative analysis in order to not only describe human condition of incertitude but also observe how the medium of literature deals with it.